2020
DOI: 10.14218/jcth.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin: An Early Warning Biomarker for Acute-on-chronic Liver Failure

Abstract: Background and Aims: Recent accumulating evidence indicates the biological actions of autotaxin (ATX) in liver disease. However, the relationship between ATX and liver failure has not been reported. The present study aimed to examine alterations of serum ATX in acute-on-chronic liver failure (ACLF) and evaluate whether serum ATX could be useful as an early warning biomarker of ACLF. Methods: Serum ATX was measured in 50 patients with hepatitis B-related ACLF, 14 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…In this regard, accessory digestive organ diseases are common in patients with AUD and have been associated with cognitive dysfunction, mainly in a range of liver diseases. Moreover, several clinical studies have suggested a potential role for ATX as a biomarker of nonalcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, accessory digestive organ diseases are common in patients with AUD and have been associated with cognitive dysfunction, mainly in a range of liver diseases. Moreover, several clinical studies have suggested a potential role for ATX as a biomarker of nonalcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significant upregulation of the ATX-LPA signaling axis has been detected in humans with different liver diseases [ 4 , 5 , 16 ]. The increased serum level of ATX is induced by a lower capacity of the liver sinusoidal endothelial cells, which causes deterioration of liver function by producing cytokines and recruiting inflammatory cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…На сегодняшний день достаточно данных, подтверждающих, что ось АТХ-LPA вовлечена в процессы инициирования и метастазирования рака, развитие атеросклероза, ожирения, артрита, глаукомы, острой и хронической печёночной недостаточности, фиброза печени, почек и лёгких и многих других заболеваний и патологических состояний [21,23,44,54,55]. Некоторые исследователи продолжают поддерживать и развивать идею о том, что данная ось играет важную роль в развитии воспаления дыхательных путей [21], в частности при БА [5,45] Можно предположить, что АТХ является относительно безопасной терапевтической мишенью, однако на сегодняшний день сведений о его безопасности для человека недостаточно [45].…”
Section: лекарственные препараты ингибирующие синтезunclassified